Medical imaging for health professionals : technologies and clinical applications - Reilly, Raymond (Hoboken, NJ : John Wiley & Sons, Inc., 2019)
'This book guides pharmacy and health researchers and professionals to understand and interpret medical imaging technology. Divided into two sections, coverage features both fundamental principles and clinical applications. It describes the most common imaging tools - X-ray, CT, ultrasound, MRI, SPECT, and PET - and their use to diagnose common diseases that include heart, cancer, and lung. In addition, the authors introduce the emerging role of molecular imaging in the management of cancer and selection of patients for personalized treatments. The book features many illustrations and provides patient case examples of imaging applications to diagnose disease or monitor therapy'--Provided by publisher.
Preface xxi -- Acknowledgments xxiii -- 1 Introduction to Medical Imaging 2 / Raymond M. Reilly -- 1.1 Medical Imaging Procedures 2 -- 1.2 Radiation Doses from Medical Imaging Procedures 4 -- 1.3 Summary 8 -- References 9 -- 2 X-Ray, CT, and Mammography Technology 11 / Raymond M. Reilly -- 2.1 Introduction 11 -- 2.2 X-Rays 11 -- 2.3 Radiography 15 -- 2.4 Computed Tomography 16 -- 2.5 Mammography 23 -- 2.6 Summary 25 -- References 26 -- Additional Reading 26 -- 3 Nuclear Medicine Imaging Technology 27 / Raymond M. Reilly -- 3.1 Introduction 27 -- 3.2 Scintillation Detectors 28 -- 3.3 The Gamma Camera 31 -- 3.4 Single Photon Emission Computed Tomography 37 -- 3.5 Positron Emission Tomography 38 -- 3.6 Multimodality Imaging -- SPECT/CT, PET/CT, and PET/MR 41 -- 3.7 Summary 42 -- References 42 -- 4 Radionuclide Production and Radiopharmaceuticals 46 / Noor Al-saden and Raymond M. Reilly -- 4.1 Introduction 46 -- 4.2 Production of Radionuclides 47 -- 4.3 Radiopharmaceutical Preparation and Supply 57 -- 4.4 Radiopharmaceuticals for Cardiac Imaging 58 -- 4.5 Radiopharmaceuticals for Tumor Imaging 63 -- 4.6 Radiopharmaceuticals for Brain/CNS Imaging 70 -- 4.7 Radiopharmaceuticals for Renal Imaging 74 -- 4.8 Radiopharmaceuticals for Hepatobiliary Imaging 76 -- 4.9 Radiopharmaceuticals for Bone Imaging 77 -- 4.10 Radiopharmaceuticals for Lung Imaging 79 -- 4.11 Radiopharmaceuticals for Thyroid/Parathyroid Imaging 80 -- 4.12 Radiopharmaceuticals for Imaging Infection/Inflammation 83 -- 4.14 Summary 85 -- Reference 85 -- Additional Reading 85 -- 5 Magnetic Resonance Imaging (MRI) Technology 87 / Raymond M. Reilly -- 5.1 Introduction 87 -- 5.2 Principles of MRI 87 -- 5.3 Components of the MRI System 98 -- 5.4 MRI Safety Considerations 100 -- 5.5 MRI Contrast Agents 102 -- 5.6 Summary 104 -- References 105 -- Additional Reading 105 -- 6 Ultrasound Imaging Technology 107 / Raymond M. Reilly -- 6.1 Principles of Ultrasound Imaging 107 -- 6.2 Doppler US 111 -- 6.3 US Contrast Agents 112 -- 6.4 Summary 113 -- References 113 -- Additional Reading 113 -- 7 Cardiac Imaging 117 / Laura Jimenez-Juan, Shaheeda Ahmed, and Katherine Zukotynski -- 7.1 Introduction 117 -- 7.2 Cardiovascular Magnetic Resonance Imaging (CMR) 117 -- 7.3 Cardiovascular MRI Techniques 118 -- 7.4 Echocardiography 129 -- 7.5 Nuclear Cardiology 133 -- 7.6 Summary 140 -- References 140 -- 8 Lung Imaging 146 / Anastasia Oikonomou -- 8.1 Introduction 146 -- 8.2 Chest Radiograph -- Projections 146 -- 8.3 Normal Findings in a Chest X-Ray 148 -- 8.4 Normal Findings in a Chest CT 155 -- 8.5 Pneumonia 158 -- 8.6 Tuberculosis 159 -- 8.7 Chronic Obstructive Pulmonary Disease 163 -- 8.8 Pleural Effusion 167 -- 8.9 Pneumothorax 169 -- 8.10 Pulmonary Embolism 170 -- 8.11 Solitary Pulmonary Nodule 172 -- 8.12 Lung Cancer 176 -- 8.13 Summary 178 -- References 180 -- 9 Breast Imaging 186 / Hemi Dua and Jagbir Khinda -- 9.1 Introduction 186 -- 9.2 Risk Factors for Breast Cancer 186 -- 9.3 Guidelines for Breast Cancer Screening 187 -- 9.4 Breast Anatomy 189 -- 9.5 Imaging Techniques 191 -- 9.6 Mammography 191 -- 9.7 Ultrasound Imaging 197 -- 9.8 Breast MRI 198 -- 9.9 PEM and Breast-Specific Gamma Camera Imaging 202 -- 9.10 Contrast-Enhanced Spectral Mammography 202 -- 9.11 The ABCs of Breast Imaging -- Image Interpretation 203 -- 9.12 BI-RADS Assessment Categories 209 -- 9.13 Image-Guided Breast Intervention 209 -- 9.14 Extramammary Staging 219 -- 9.15 Breast Lymphoscintigraphy 220 -- 9.16 Summary 220 -- References 220 -- 10 Endocrine Gland Imaging 225 / Katerina Mastrocostas, Kim May Lam, Shereen Ezzat, and Sangeet Ghai -- 10.1 Introduction 225 -- 10.2 The Thyroid Gland 225 -- 10.3 Thyroid Hormone Diseases 227 -- 10.4 Thyroid Cancer 240 -- 10.5 The Parathyroid Glands 244 -- 10.6 The Adrenal Glands 249 -- 10.7 Mass Lesions of the Adrenal Cortex 250 -- 10.8 Mass Lesions of the Adrenal Medulla 253 -- 10.9 Other Neuroendocrine Diseases 255 -- 10.10 Summary 259 -- Additional Reading 260 -- 11 Abdominal Imaging 264 / Vivek Singh and Chirag Patel -- 11.1 Introduction 264 -- 11.2 Surgical Sieve 265 -- 11.3 Peritoneum/Mesentery 265 -- 11.4 Acute Peritoneal Pathologies 266 -- 11.5 Gastrointestinal Tract 270 -- 11.6 Inflammatory Bowel Disease 279 -- 11.7 Colorectal Adenocarcinoma 282 -- 11.8 Hepatic System 287 -- 11.9 Diffuse Hepatic Disease 289 -- 11.10 Focal Hepatic Disease 292 -- 11.11 Biliary Tract 300 -- 11.12 Gallbladder 301 -- 11.13 Bile Ducts 304 -- 11.14 Pancreas 306 -- 11.15 Spleen/Lymph Nodes 313 -- 11.16 Summary 316 -- Reference 317 -- Additional Reading 317 -- 12 Genitourinary Tract Imaging 320 / Sarah Johnson -- 12.1 Introduction 320 -- 12.2 GU System Imaging Modalities 321 -- 12.3 Evaluation of the Kidneys and Collecting Systems 328 -- 12.4 Bladder and Urethra 343 -- 12.5 Testicles 345 -- 12.6 Prostate 348 -- 12.7 Female Genitourinary Tract 350 -- 12.8 Pediatric Genitourinary Tract 360 -- 12.9 Summary 364 -- References 364 -- 13 Imaging of the Head, Neck, Spine, and Brain 371 / Laila Alshafai, Eugene Yu, and Sylvain Houle -- 13.1 Introduction 371 -- 13.2 Imaging the Skull and Brain 372 -- 13.4 Imaging the Head and Neck 390 -- 13.5 PET and SPECT Neuroimaging 396 -- 13.6 Summary 401 -- References 401 -- 14 Musculoskeletal Imaging 404 / Rakesh Mohankumar and Ali Naraghi -- 14.1 Introduction 404 -- 14.2 Plain Radiography (X-rays) 404 -- 14.3 Computed Tomography 408 -- 14.4 Magnetic Resonance Imaging 411 -- 14.5 Ultrasound 413 -- 14.6 Applications of Musculoskeletal Imaging 415 -- 14.7 Summary 435 -- Additional Reading 435 -- 15 Molecular Imaging with Positron Emission Tomography 439 / Ur Metser, Noam Tau, and Amit Singnurkar -- 15.1 Introduction 439 -- 15.2 PET Probes Including 18F-FDG 440 -- 15.3 18F-FDG PET in Oncology 442 -- 15.4 18F-FDG PET in Non-Oncology Indications 453 -- 15.5 Overview of Other PET Radiopharmaceuticals 460 -- 15.6 Multimodal Imaging -- PET/CT Versus PET/MR 468 -- 15.7 Summary 470 -- References 470 -- Index 485
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Diagnostic imaging; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; Diagnostic imaging; Diagnostic imaging -- Methods; Electronic books; Electronic books